Influence of antibiotic exposure in the early postnatal period on the development of intestinal microbiota - Tanaka, Shigemitsu; Kobayashi, Takako; Songjinda, Prapa; Tateyama, Atsushi; Tsubouchi, Mina; Kiyohara, Chikako; Shirakawa, Taro; Sonomoto, Kenji; Nakayama, Jiro (FEMS immunology and medical microbiology, 2009)
The influence of antibiotic exposure in the early postnatal period on the development of intestinal microbiota was monitored in 26 infants including five antibiotic-treated (AT) subjects orally administered a broad-spectrum antibiotic for the first 4 days of life and three caesarean-delivered (CD) subjects whose mothers were intravenously injected by the similar type of antibiotics in the same period. The faecal bacterial composition was analysed daily for the first 5 days and monthly for the first 2 months. Terminal restriction fragment length polymor-phisms in the AT subjects showed less diversity with the attenuation of the colonization of some bacterial groups, especially in Bifidobacterium and unusual colonization of Enterococcus in the first week than the control antibiotic-free infants (AF, n=18). Quantitative real-time PCR showed overgrowth of enterococci (day 3, P=0.01; day 5, P=0.003; month 1, P=0.01) and arrested growth of Bifidobacterium (day 3, P=0.03) in the AT group. Furthermore, after 1 month, the Enterobacteriaceae population was markedly higher in the AT group than in the AF group (month 1, P=0.02; month 2, P=0.02). CD infants sustained similar, although relatively weaker, alteration in the developing microbiota. These results indicate that antibiotic exposure at the beginning of life greatly influences the development of neonatal intestinal microbiota.